Paravalvular sealing pf percutaneous heart valves - Conradie, David Gideon (Division of Cardiothoracic Surgery, 2022)
Paravalvular regurgitation (PVR), which frequently occurs after transcatheter aortic valve replacements (TAVR) can lead to adverse clinical consequences and has been shown to correlate to an increased late mortality and morbidity. Quantification, graduation and testing for PVR has proven challenging and a standardized method for pre-clinical testing is still sought. Commercial transcatheter heart valves (THV's) rely on sealing skirts made from treated pericardium or polyethylene terephthalate (PET) fabrics. The current study was aimed at developing novel electrospun skirts for the minimization of PVR in THV's. Thermoplastic polyurethane (TPU) was electrospun onto mandrels and several techniques (CO2 - laser, ultra-sonic, solvent and conductive heat bonding) used to attach the scaffolds to pre-coated TAVR stents. Attachment strength was modelled by finite element analysis (FEA) of stents in the crimped and expanded conditions and empirically determined by physical pull-off tests. PVR was evaluated for four different skirt designs (1× single layer “FLAT” and 3× double layers: Forward Flow Filling “FFF”, No Filling “NF” and Back Flow Filling “BFF”) using a pulse duplicator fitted with perforated mounting rings. Optimization of solution, process and environmental parameters yielded scaffolds with average fibre diameters of 3.17 ± 0.64 μm and average pore sizes 9.52 ± 6.90 μm. Tensile strength was found to be similar in the direction perpendicular to collector rotation